Metformin enhances epithelial cell growth inhibition via the protein kinase–insulin-like growth factor binding protein-1 pathway - Xuping Shao; Changling Li; Junhui Liang; Li Changzhong (Journal of Obstetrics and Gynaecology)
Background Abnormal stromal-epithelial cell communication is a pathogenic mechanism in endometriosis, and metformin can modulate it. Insulin-like growth factor binding protein-1 (IGFBP1) plays a role in endometriosis, but the exact mechanism is unknown. IGFBP1 is reportedly a downstream target of metformin in some diseases. We aimed to investigate the role of IGFBP1 in endometriosis development, whether it is associated with abnormal communication, and whether metformin affects IGFBP1 expression.Methods Patients who underwent surgical treatment for endometriosis or other diseases were enrolled. Ten patients with ovarian-type endometriosis and eight patients each who underwent surgical treatment for other lesions with or without endometriosis were selected, and their tissues taken for cell proliferation, western blotting, polymerase chain reaction, and knockdown experiments.Results Ectopic and eutopic stromal cells (EcSCs and EuSCs) lost their ability to inhibit epithelial cell proliferation, and IGFBP1 expression was downregulated in both groups of stromal cells compared to that in normal stromal cells (NSCs; 1.09 vs. 0.25, p = .0002 1.09 vs. 0.57, p = .0029). In an EcSC IGFBP1 overexpression model, the ability of EcSCs to inhibit epithelial cell proliferation was enhanced (EdU positivity decreased from 38% to 25%, p = .0001). Furthermore, adenosine 5’-monophosphate-activated protein kinase (AMPK) phosphorylation was downregulated in EcSCs and EuSCs compared to that in NSCs (0.99 vs. 0.42, p = .0006/0.99 vs. 0.57, p = 0.0032). Treatment of EcSCs with metformin increased AMPK phosphorylation (0.47 vs. 1.04, p = .0107) while upregulating IGFBP1 expression (0.69 vs. 1.01, p = .0164), whereas pre-treatment with an AMPK phosphorylation inhibitor abrogated metformin-induced IGFBP1 upregulation.Conclusions IGFBP1 mediates aberrant stromal-epithelial communication in endometriosis. Metformin can upregulate IGFBP1 expression in EcSCs by activating AMPK, and upregulated IGFBP1 enhances the inhibition of epithelial cell proliferation. IGFBP1 is expected to be a therapeutic target for endometriosis.